Assessing the burden of illness from cervical dystonia using the Toronto Western Spasmodic Torticollis Rating Scale scores and health utility: a meta-analysis of baseline patient-level clinical trial data. (29th August 2014) - Jen, Min-Hua; Kurth, Hannah; Iheanacho, Ike; Dinet, Jerome; Gabriel, Sylvie; Wasiak, Radek; Jost, Wolfgang H.
Abstract: Purpose: This study aimed to explore the burden of illness associated with cervical dystonia (CD), including possible demographic and humanistic correlates of baseline disease severity. Methods: The analysis involved the five multinational randomized, placebo-controlled clinical trials that had evaluated the efficacy and safety of Dysport® in patients with CD, including assessment using the Toronto Western Spasmodic Torticollis Rating Scale (TWSTRS). Patient-level TWSTRS scores from the individual studies were meta-analysed to estimate disease severity at baseline. One of the studies had reported Short Form-36 (SF-36) Health Survey quality-of-life measures, and these data were used to investigate whether the severity of CD was associated with humanistic outcomes, as measured by health utility. A generalized regression model was then applied to explore potential correlation between TWSTRS scores and utilities. Results: The estimated pooled mean baseline severity of CD in clinical trial entrants, as measured by TWSTRS score, was 43.23 (95% CI = 39.31–47.15). In general, disease severity was significantly greater in patients aged over 40 years (compared to the reference group aged 18–30 years). However, there was no correlation between disease severity and other demographic characteristics (e.g., weight, height, gender). Higher TWSTRS scores correlated with worse health-related quality of life as perceived by patients and was reflected in health utility ( R 2  = 0.133). Conclusions: This study was able to define TWSTRS scores in patients with CD in terms of associated utility. This approach could help in capturing the disease's burden through measures that are more tangible than TWSTRS scores to patients, carers, clinicians, and healthcare payers.